INI1-Intact Sinonasal Carcinoma with Rhabdoid Features. (18th November 2021) - Mulry, Erin; Blake, Danielle M.; Hegde, Poornima; Falcone, Todd E.
Abstract : Sinonasal malignancies are known for their associated poor prognosis and diversity of histologic features. While poor prognosis is largely due to advanced disease at presentation, histologic features also play a significant role. Therefore, accurate pathologic diagnosis is of utmost importance. Here, we describe a 63-year-old male with chronic left-sided nasal obstruction and left-sided epistaxis who was found to have a large mass occupying most of the nasal cavity extending through the nasopharynx to just below the nasopharyngeal surface of the soft palate. During surgical excision, the mass was noted to originate from the floor of the maxillary sinus with erosion of the medial wall of the maxillary sinus. Pathology revealed a diagnosis of INI1-intact poorly differentiated composite carcinoma with rhabdoid phenotype and sarcomatoid and squamous cell carcinoma foci arising within an inverted papilloma. Included in this report is a detailed description of both the patient's medical course and this pathologically novel sinonasal neoplasm. We aim to elucidate this rare tumor's complex features in order to improve future diagnosis and stimulate prospective research on sinonasal malignancies with complex histology.